A formação do coordenador pedagógico com base em premissas do pensamento sistêmico e na educação das emoções de Martha Nussbaum - Mora, Neura (2024)
This dissertation is the result of research developed in the Postgraduate Program in Education (PPGEdu), at the University of Passo Fundo, Rio Grande do Sul. The study discusses the role of the pedagogical coordinator, seeking to investigate the premises of a process of establishment of lines of work that respect the different contexts of pedagogical coordinators at school units, justifying the importance of the qualified work of this professional at school. The research question is formulated as follows: What are the contours of the training of pedagogical coordinators as articulators of educational processes capable of considering different themes, based on the premises of systemic thinking and Martha Nussbaum's education of emotions? The general objective lies in investigating the training processes of pedagogical coordinators and the conceptions about their role, exploring possibilities of theoretical approaches to the systemic thinking of Maturana and Varela and the education of emotions by Martha Nussbaum. The specific objectives are set to: explore the theoretical-methodological conceptions of the role of the pedagogical coordinator in the 21st century; analyze the premises of systemic thinking by deepening concepts in Maturana and Varela; approach Martha Nussbaum's education of emotions as foundations for the training of pedagogical coordinators; and, finally, collectively produce indications for the elaboration of a proposal for continued training for pedagogical coordinators, in a reflective and humanizing line of work, observing their contexts of action. As qualitative research, the dissertation proposes the carrying out of participatory research, through a collaborative methodological approach. The data collection instrument is the questionnaire, with analysis through categorization of generated data and, from this, the constitution of a focus group, which aims to enable collective analysis of theoretical concepts, in order to provide support for action. of these professionals in their school context. This context demands theoretical-reflexive processes, supported by works by authors such as Vasconcellos (2019), Libâneo (2018), Maturana and Varela (2021), Nussbaum (2015), Fávero et al. (2021), Placco and Almeida (2009, 2015, 2018) and Sartori (2022), among others. When considering the possibility of collective formative moments, it is possible to think from new paradigms and expand perceptions about education and training, as well as linking the education of emotions as an important factor in the constitution of subjects and in the teaching and learning processes. In this way, it is possible to see that, providing opportunities for the construction of training processes in a collective and collaborative way, between peers, in a process that gains space and strength in education. This process enables a differentiated proposal, not in the sense of replacing what already exists, but of complementing and giving new meaning to concepts, allowing assertive and systemic educational connections, which prioritize relationships between subjects. The results of this investigation demonstrate the importance of reflective training for the pedagogical coordinator, as a way of appropriating concepts, enabling new ways of acting in their reality. Such training can promote qualitative changes in you, as a professional, in the school community and also in society as a whole.